The Barriers of Antenatal Care Visits in Rural Mother’s Community in Padang Lawas Regency: A Qualitative Study - Ariescha, Putri Ayu Yessy; Machmud, Rizanda; Ocviyanti, Dwiana; Syah, Nur Afrainin; Yusrawati, Yusrawati; Bachtiar, Adang; Chatra, Emeraldy; Yani, Finny Fitry (GLOBAL HEALTH SCIENCE GROUP, 2024)
The low utilization of antenatal care services has an impact on the condition of the pregnancy not being monitored which will cause danger signs of pregnancy to go undetected and can lead to maternal death. Padang Lawas is the area with the lowest coverage of antenatal care visits in north Sumatra province. The majority of pregnant women in Padang Lawas district do not receive standard antenatal care services. Efforts to increase coverage rates for Antenatal Care visits have been carried out by the Health Service but have not produced any real impact. Objective: This study aims to find out more about the perspective of antenatal care visits for pregnant women. Method: This study was qualitative with a grounded theory approach. The informants in this study were 5 mothers, 5 husbands, 3 midwives, and 1 community figure who were recruited using purposive sampling. Data were collected using semi-structured interviews. Data were analyzed using the Content Analysis. Results: The study emerged 4 themes: (1) Culture about pregnancy, (2) Infrastructure in antenatal care, (3) Economic issues, and (4) Mother's behavior in carrying out antenatal care. Conclusions: The findings show that there are several barriers of antenatal care visits in rural maternal communities, so the government needs to pay attention to them in following up on the barriers found in these areas.